RANCANG BANGUN SISTEM OTOMATISASI PADA CUSTOM ICE CRYSTAL MACHINE - Mokhamad Rizki Febriansyah; Muh Anis Mustaghfirin; Aminatus Sa’diyah (Proceedings Conference on Marine Engineering and its Application, 2020)
Ice crystal is a daily needs for consumables, so that it needs an inovation that serves as asupport to sover the needs of ice crystal. For the performance of tools needed automation made tofacilitate the performance of this ice crystal machine, with the main drive of the DC motor made forthe ups and downs of the plate as a mold for this ice crystal, then in the automation writer usesArduino as a micro-controller that will capture the DS18B20 sensor. with a DS18B20 sensor that cancapture sensors below -55 ? so that when the ice crystal is frozen the sensor will read and move theDC stepper motor that makes the automatic plate down and the ice crystal attached to the evaporatorwill be released with a reverse process on the system. Ice crystal will fall automatically and prepare atray as a base to hold the ice.